2009
DOI: 10.1021/ac9015159
|View full text |Cite
|
Sign up to set email alerts
|

High Wavenumber Raman Spectroscopy for in Vivo Detection of Cervical Dysplasia

Abstract: Raman spectroscopy is a vibrational spectroscopic technique capable of optically probing the biomolecular changes associated with neoplastic transformation. The purpose of this study was to apply near-infrared (NIR) Raman spectroscopy in the high wavenumber (HW) region (2800-3700 cm(-1)) for in vivo detection of cervical dysplasia. A rapid-acquisition NIR Raman spectroscopy system associated with a ball-lens fiber-optic Raman probe was developed for in vivo spectroscopic measurements at 785 nm excitation. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 47 publications
3
162
0
2
Order By: Relevance
“…Over the past three decades, there has been tremendous growth worldwide of optical spectroscopic techniques (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) using 785 nm laser light from diode lasers, especially in Raman spectroscopic characterization and discrimination of breast malignancy (6,18,19,(25)(26)(27). However, few works disclose resonance Raman spectra differences of the cancerous and normal tissues and study biological basis of these differences (12).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, there has been tremendous growth worldwide of optical spectroscopic techniques (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) using 785 nm laser light from diode lasers, especially in Raman spectroscopic characterization and discrimination of breast malignancy (6,18,19,(25)(26)(27). However, few works disclose resonance Raman spectra differences of the cancerous and normal tissues and study biological basis of these differences (12).…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced metabolic rate in colonic cancer [36] contributes to the increased water content as water provides the conversion of mechanical energy developed by contractile proteins into the chemical energy useful in cell process [37]. The increased water for the cancerous colonic tissue has also been observed in other cancer tissues (e.g., esophagus [28], stomach [38], cervix [39][40][41] and brain [42]) by using Raman spectroscopy [4,28,[38][39][40][41][42]. We have also found the decreased DR of hemoglobin band (940 nm) for the colonic cancer, signifying the increased hemoglobin content associated with colonic cancer tissue.…”
Section: Resultsmentioning
confidence: 99%
“…It provides a chemical fingerprint of a sample, that can be used to distinguish diseased tissue from healthy [254,255], and is especially promising for diagnosis of early stage cancer or pre-cancer conditions [256,257]. Patil et al showed that data from Raman spectroscopy can help to accurately classify skin lesions when OCT images alone are ambiguous [258,259].…”
Section: Combination Of Modalitiesmentioning
confidence: 99%